Techniques In Teaching Reading To The Seventh Grade Of Smp Negeri 2 Wonogiri - Ahsan, Annisa, Aryati Prasetyarini, S.Pd, M.Pd, Nur Hidayat, M.Pd (2015)
Annisa Ahsan. A320110023. TECHNIQUES IN TEACHING READING TO THE SEVENTH GRADE OF SMP NEGERI 2 WONOGIRI. Research Paper. Teacher Training and Education Faculty. Muhammadiyah University of Surakarta. 2015. The objectives of the study are to identify the techniques in teaching reading and the procedures of teaching reading to the seventh grade of SMP Negeri 2 Wonogiri. This study is descriptive qualitative research. The data are taken from observation, interview, and documentation. In collecting the data, the writer employs observation and interview. The techniques for analyzing data are data reduction, data display, and conclusion drawing. The results of this study are: (1) the techniques in teaching reading to the seventh grade in SMP Negeri 2 Wonogiri are reading aloud and KWLH technique, (2) the procedures of teaching reading consists of pre-reading, while-reading and post-reading.